Employability Challenges Among Recidivists: A Qualitative Study - Wan Muda, Wan Hanem Nazira; Abdullah, Nurul Hidayah Liew; Paimin, Aini Nazura; Hamid, Hashima; Yuying, Zhu (Journal of Technical Education and Training, 2023)
Crime is a social phenomenon in almost every country. The increasing of crime incidents every now and then could instigate recurrence of crimes. The integration of prison inmates into society after release is a challenging phase to start anew outside the iron curtain. As such, this group might tend to return to prison. Therefore, this study aims to explore recidivism among recidivists towards employability. The design of this study is narrative by using a qualitative approach and aided by a semi-structured interview protocol to facilitate the data collection process. A total of 5 recidivists from a prison around the southern zone were selected as study participants. The interviews obtained were analyzed using thematic analysis. The results of the study found that there are four recidivist factors returning to prison, namely difficulty in finding a job, unwillingness to change, family and community stigma, and the relaxation of conditions for participating in the Human Rehabilitation Program (PPI). In conclusion, apart from difficulties in securing employment, there are other reasons that cause recidivism to occur. Therefore, the researcher suggests that the PPI provided by the prison to be updated in line with the needs of recidivists from physical aspects, personality, skills and integration into society so that recidivism cases could be reduced.